Islamic Stock Market Reaction To The Russia-Ukrainian War - Farah Faadilah; Atina Shofawati (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to analyze stock market reaction events preceding and following the proclamation of the Russian invasion of Russia for companies listed on the Indonesia Stock Exchange and indexed by the Jakarta Islamic index. This investigation employs a quantitative approach with an event study methodology. The sample consists of thirty shares of companies listed on the Jakarta Islamic Index. The research sample was selected using the technique of purposive sampling. The research data were analyzed utilizing the paired sample t-test method. The findings of this study indicate that the anomalous return variable affects Jakarta Islamic Index stock prices differently before and after the announcement of the Russian invasion of Ukraine. Before and after the proclamation of the Russian invasion of Ukraine, there is a difference in the trading volume of stocks included in the Jakarta Islamic Index. Investors need to reallocate their assets strategically by developing a hedging strategy to avoid the risk of global uncertainty induced by unpredictability. Investors must invest long-term in anticipating speculators on the capital market, who can cause aberrant returns and abnormal stock trading volatility. To stabilize the stock market, regulators should consider the adverse effects of the financialization/globalization of the stock market in terms of war/conflict. Speculators prey on the uncertainty of global events, which leads to tyranny and abnormal rates of abnormal returns.